Genome assembly of Mechow's mole-rat (Fukomys mechowii) as a prerequisite for the analysis of transposon expression in mole-rat oocytes. - Tolar, Nikolas (Jihočeská univerzita, 2023)
This thesis presents the results of Mechow's mole-rat (Fukomys mechowii) genome assembly, as well as explores transposon content in RNA-seq data from oocytes of several mammalian species.
Genome assembly of Mechow's mole-rat (Fukomys mechowii) as a prerequisite for the analysis of transposon expression in mole-rat oocytes.
Keywords: naked mole-rat; mechow's mole-rat; transposable element; transposon; oocyte; genome assembly; RNA-seq; transposon expression; genome annotation; naked mole-rat; mechow's mole-rat; transposable element; transposon; oocyte; genome assembly; RNA-seq; transposon expression; genome annotation